2017
DOI: 10.1007/s10571-017-0549-2
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Generate Pericytes in the Developing Brain

Abstract: Pericytes are defined by their anatomical location encircling blood vessels' walls with their long projections. The exact embryonic sources of cerebral pericytes remain poorly understood, especially because of their recently revealed diversity. Yamamoto et al. (Sci Rep 7(1):3855, 2017) using state-of-the-art techniques, including several transgenic mice models, reveal that a subpopulation of brain pericytes are derived from phagocytic macrophages during vascular development. This work highlights a new possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…The hematopoietic stem cells, which give rise to all blood and immune cells throughout life, reside in a specific complex niche in the bone marrow, that supports the homeostasis of these cells, composed by osteoblasts, osteocytes, osteoclasts, endothelial cells, adipocytes, smooth muscle cells, pericytes, fibroblasts, macrophages, megakaryocytes, lymphocytes, hematopoietic progenitors, neutrophils, peripheral innervations, and Schwann cells [18,85,64,8689,19,9,10,90,93]. Recent studies have revealed distinct contributions of several cellular components of the bone marrow to different functions of hematopoietic stem cells regulation.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
“…The hematopoietic stem cells, which give rise to all blood and immune cells throughout life, reside in a specific complex niche in the bone marrow, that supports the homeostasis of these cells, composed by osteoblasts, osteocytes, osteoclasts, endothelial cells, adipocytes, smooth muscle cells, pericytes, fibroblasts, macrophages, megakaryocytes, lymphocytes, hematopoietic progenitors, neutrophils, peripheral innervations, and Schwann cells [18,85,64,8689,19,9,10,90,93]. Recent studies have revealed distinct contributions of several cellular components of the bone marrow to different functions of hematopoietic stem cells regulation.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
“…They communicate with endothelial cells along the length of the vasculature by physical contacts and paracrine signaling (Birbrair et al, ). In the central nervous system, the ratio of pericytes to endothelial cells is approximately 1:1 (Shepro & Morel, ), indicating the enormous importance of pericytes in the central nervous system physiology (Almeida et al, ; Birbrair et al, ; Coatti et al, ; Prazeres et al, ; Santos, Prazeres, Mintz, & Birbrair, ). Novel approaches which combine anatomical location with expression of multiple molecular markers, and with genetic lineage tracing became available recently, contributing to the progress in the understanding of pericytes function in health and disease (Birbrair et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…31 Parfejevs et al exhibit that Schwann cells up-regulate the expression of PDGFβ after dermal lesion. 12 Interestingly, several stromal cells present in the skin microenvironment, important in wound healing progress, express the cell-surface tyrosine kinase receptor, PDGFRβ, such as pericytes, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] vascular smooth muscle cells, 46,47 and tissue-resident fibroblasts. 48 Therefore, PDGFβ/PDGFRβ signaling may play crucial role in the communication between these important cell types during dermal healing.…”
Section: Schwann Cells Derived Signals Important After Cutaneous Injurymentioning
confidence: 99%